How much did you actually drink last night? An evaluation of standard drink labels as an aid to monitoring personal consumption - Osiowy, M.; Stockwell, Tim; Zhao, J.; Thompson, K.; Moore, S. (Informa Healthcare, 2015)
Background: Barriers exist for drinkers who wish to comply with low-risk guidelines when these are expressed in terms of numbers of “standard drinks” of alcohol. The increasing variability of container sizes and alcoholic strengths mean that percent alcohol by volume (%ABV) labels alone may be insufficient. Aims: To investigate whether standard drink (SD) labels would improve drinkers’ accuracy when estimating personal alcohol consumption. Setting: Private liquor stores near the University of Victoria, BC. Design: A 2 × 3 × 3 experimental design was employed with two labels (%ABV and SD), three beverages (beer, wine, and spirits) and three beverage strengths in balanced order. Subjects estimated the number of standard drinks that would be consumed in scenarios involving containers of their preferred beverages presented with different labels. Participants: A convenience sample of 301 liquor store patrons, aged 19 years and over. Measurements: Participants’ accuracy was determined by the relative and absolute percent errors in their estimations in comparison with correct answers. Results: Estimates were significantly more accurate with SD than %ABV labels in almost all the scenarios. Significantly more underestimation errors were made with %ABV labels. Mixed model regression analysis indicated younger respondents, beer drinkers and those with higher education made significantly fewer errors. Most (82.7%) supported SD labelling and believed SD labels would help them to comply with low-risk drinking guidelines (68.3%). Conclusions: The addition of clear SD labels helps consumers to make more accurate estimates of the SD content of their usual beverages than %ABV labels alone and would be more likely to help them comply with drinking guidelines.